Gåvoekonomin i det modema samhället (Sociologisk Forskning, 2001)
The gift-economy in the modern societyIn the article it is argued that the institution of the gift - analysed ever since Marcel Mauss influential essay from 1925 “The Gift” - still is of sociological interest. The article proceeds by comparing the gift-economy to the market economy, which is done in six subsequent steps: 1. The private and public spheres of the gift. 2. The social mechanisms misrecognition of the gift. 3. The gift as aninalienable possession. 4. The functional redundancy of the gift from an economical viewpoint. 5. The excluding characteristics of the gift-institution. 6.Competitive behaviour within the bounds of the gift-institution. On the basis of this argument, it is argued, firstly, that the gift institution works through strong informal and institutionalised norms that are important for the co-ordination of exchanges in a modern society, not just the archaic societies analysed by Mauss. Secondly, it is argued that the effects of the gift-economy on social relations have great impact on the workings of everyday economic exchanges, especially in the local and regional context.
Keywords: gift-economy; reciprocity; norms